Significant prevalence of peripheral artery disease in patients with disturbed wound healing following elective foot and ankle surgery: Results from the ABI-PRIORY (ABI as a PRedictor of Impaired wound healing after ORthopedic surgerY) trial. (April 2020) - Müller, Arne M; Toepfer, Andreas; Harrasser, Norbert; Haller, Bernhard; Walther, Markus; von Eisenhart-Rothe, Rüdiger; Gemperlein, Karla; Bergmann, Katharina; Bradaric, Christian; Laugwitz, Karl-Ludwig; Ibrahim, Tareq; Dirschinger, Ralf J
Disturbed wound healing (DWH) following elective foot and ankle surgery is associated with a number of known risk factors. The purpose of this study was to determine if peripheral artery disease (PAD) is a potential risk factor that contributes to an increase in postoperative DWH. In a case–control study, we analyzed all patients undergoing elective foot and ankle surgery between January 1, 2014 and December 31, 2017 at two institutions and identified 51 patients with postoperative DWH. After matching with 51 control patients without DWH, all 102 patients were evaluated for PAD. The prevalence of PAD was significantly higher in the DWH group compared to the control group (41.2% vs 19.6%, p < 0.01). This difference was even more distinctive for patients with any abnormal ankle–brachial index (ABI) (51.0% vs 19.6%, p < 0.001). After adjustment for diabetes, hypertension, hypercholesterolemia, and smoking, any abnormal ABI or a history of PAD remained an independent risk factor for DWH (odds ratio 3.28; 95% CI 1.24–8.71). In this dual-center study, postoperative DWH was associated with significantly higher rates of PAD. These findings suggest that preoperative evaluation for PAD could be a helpful tool to identify patients at high risk for postoperative wound complications undergoing foot and ankle surgery.This trial is registered with drks.de, number DRKS00012580.